Mapping the attainment of health promotion competencies: Implications for credentialing and professional development - Maycock, Bruce; Howat, Peter; Hazell, F. (Australian Council for Health, Physical Education and Recreation, 2004)
This article documents the development of an evidence guide, which maps the attainment of nationally identified health promotion competencies by students completing the undergraduate or postgraduate course in health promotion at a large Australian university. Using an action research process an evidence guide was developed that met the needs of key stakeholders. This is the first time any Australian university has utilized the national competencies in this way. The evidence guide is a document that collates evidence of attainment of health promotion competencies. It can be used by students as a planning tool and as an aid to gaining employment. It also has the potential to be used as part of a credentialing process for health promotion practitioners.